Influence of copper sulfate and tribasic copper chloride on feed intake preference in finishing pigs - Kyle F Coble; Korrin N Card; Joel M DeRouchey; Michael D Tokach; Jason C Woodworth; Robert D Goodband; Steven S Dritz; J Usry (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 150 pigs (PIC 327 × 1050; initially 191 lb BW) were used in a 15-d study to determine if pigs have a preference for diets that contain added Cu from either copper sulfate (CuSO4) or tribasic copper chloride (TBCC). Pens of pigs were randomly allotted to 1 of 3 dietary preference comparisons with 10 replications per comparison. Treatment diets used were a corn-soybean meal control with no supplemental Cu, or the control diet with 150 ppm of added Cu from either CuSO4 or TBCC. Pens contained two feeders, each with 1 of 2 treatment diets with feeders rotated once daily within each pen. The comparisons tested were: (1) control vs. CuSO4, (2) control vs. TBCC, and (3) CuSO4 vs. TBCC. For comparison 1, pigs consumed more (P<0.01) of the control diet than the added CuSO4 diet (3.68 vs. 2.02 lb/d), which translated into pigs eating 66% of their daily intake from the control diet and 34% from the CuSO4 diet. For comparison 2, pigs consumed more (P<0.03) of the control diet than the TBCC diet (3.30 vs. 2.49 lb/d), which equated to 57% of their daily intake from the control diet and 43% from the TBCC diet. For comparison 3, pigs consumed more (P<0.01) of the diet containing TBBC than that with the added CuSO4 (3.50 vs. 1.96 lb/d), which was equivalent to 65% vs. 35% of daily intake, respectively. In summary, when given a choice, pigs preferred to consume a diet without high levels of added Cu; however, when given the choice between diets containing either Cu source, pigs preferred diets containing TBCC.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Finishing pig; Copper; Feed intake; Preference